CAUSES OF UNDER-FIVE MORTALITY IN DISTRICT QUETTA BALOCHISTAN - Safia Habib; Prof, Dr. Rana Saba Sultan (International Journal of Contemporary Issues in Social Sciences, 2023)
Child mortality in underdeveloped nations, including Pakistan, is a crucial well-being indicator shaped by diverse factors. The occurrence of child mortality is associated with various socioeconomic factors the most important is maternal education. Pakistan has made noteworthy progress in reducing child mortality over the years, transitioning from 141 deaths per 1,000 live births in 1990 to 69.5 deaths per 1,000 live births in 2019. However, Balochistan, one of Pakistan’s provinces, stands out with notably high maternal mortality rates (298 deaths per 1,000 live births), the highest Infant Mortality Rate (IMR) at 48, and the highest under-5 mortality rate (U5MR) at 53. This research study investigates the underlying causes of under-five mortality, focusing on the level of parental education associated with under–five mortality within the Quetta district. The investigation focused on child mortality in peri-urban areas of the Quetta district, utilizing an explanatory sequential mixed-methods approach. A sample of 400 families, representing 216,352 children aged 0-59 months, was selected through a multistage sampling process. Quantitative data collected via survey interviews underwent thorough statistical analysis using bivariate and multivariate logistic regression in SPSS (version 20). Simultaneously, qualitative insights were extracted from 12 health professionals through purposive sampling and two focus group discussions. The information about mothers’ educational background revealed that a sizable number of mothers were illiterate, with 317 participants (or 79.3%) falling into this category. Additionally, 74 participants (18.5%) had an elementary education, while only nine participants (2.3%) had a secondary education. While, father’s education contains those 213 individuals, or 53.3% were determined to be illiterate, while others had varied degrees of education. To be more specific, 108 individuals (27.0%) had completed their primary education. A smaller proportion had completed their secondary education (58/ 14.5%), gained matriculation (12/3.0%), or even graduated (9/2.3%). When mother education was examined, it was discovered that illiterate women have a higher risk of their children dying before age five (p = 0.005). Maternal education significantly influences child mortality rates, as affirmed by both healthcare professionals’ observations and existing literature. Educated parents are better equipped with essential knowledge about prenatal and postnatal care, can recognize warning signs of illness in their children, adhere to recommended health practices, and seek timely medical care. The promotion of parental education emerges as a fundamental strategy in the global effort to reduce child mortality and provide every child with a chance to thrive.